Tumor suppressor candidate 3 (TUSC3) prevents the epithelial-to-mesenchymal transition and inhibits tumor growth by modulating the endoplasmic reticulum stress response in ovarian cancer cells - Kratochvílová, Kateřina; Horak, Peter; Ešner, Milan; Souček, Karel; Pils, Dietmar; Anees, Mariam; Tomasich, Erwin; Dráfi, František; Jurtíková, Veronika; Hampl, Aleš; Krainer, Michael; Vaňhara, Petr (International journal of cancer, 2015)
Ovarian cancer is one of the most common malignancies in women and contributes greatly to cancer-related deaths. Tumor suppressor candidate 3 (TUSC3) is a putative tumor suppressor gene located at chromosomal region 8p22, which is often lost in epithelial cancers. Epigenetic silencing of TUSC3 has been associated with poor prognosis, and hypermethylation of its promoter provides an independent biomarker of overall and disease-free survival in ovarian cancer patients. TUSC3 is localized to the endoplasmic reticulum in an oligosaccharyl tranferase complex responsible for the N-glycosylation of proteins. However, the precise molecular role of TUSC3 in ovarian cancer remains unclear. In this study, we establish TUSC3 as a novel ovarian cancer tumor suppressor using a xenograft mouse model and demonstrate that loss of TUSC3 alters the molecular response to endoplasmic reticulum stress and induces hallmarks of the epithelial-to-mesenchymal transition in ovarian cancer cells. In summary, we have confirmed the tumor-suppressive function of TUSC3 and identified the possible mechanism driving TUSC3-deficient ovarian cancer cells toward a malignant phenotype.
Keywords: Animals; tumor supresorové geny; nádory vaječníků; Female; myši SCID; Cell Line, Tumor; ženské pohlaví; Epithelial-Mesenchymal Transition; nádorové supresorové proteiny; Heterografts; lidé; Mice; Ovarian Neoplasms; myši inbrední NOD; membránové proteiny; Mice, SCID; myši; stres endoplazmatického retikula; Mice, Inbred NOD; Tumor Suppressor Proteins; Endoplasmic Reticulum Stress; Membrane Proteins; epitelo-mezenchymální tranzice; zvířata; heterografty; nádorové buněčné linie; Genes, Tumor Suppressor; Humans